Multidisciplinary therapy strategy of precision medicine in clinical practice. Issue 1 (31st March 2020) - Qian, Mengjia; Li, Qian; Zhang, Miaomiao; Xu, Xiaojing; Shen, Qi; Chen, Hao; Wang, Xiangdong; Liu, Tianshu; Cheng, Yunfeng
Abstract: The application of precision medicine concept in clinical work needs a period of practice and experience accumulation. The present article introduced an example of functioning approach named "multidisciplinary therapy strategy of precision medicine" (MDTS‐PM), clinical practice and process, decision‐making, and therapies. The MDTS‐PM integrates multidisciplinary experts and develops real‐time therapeutic strategy based on clinical phenomes and gene sequencing of tissue DNA and circulating DNA. The strength of MDTS‐PM is the combination of dynamical clinical phenomes, genetic information, diagnosis, and treatment to make the therapy more targeted and specific. MDTS‐PM provides comprehensive, whole‐process, and personalized diagnosis and treatment services for patients with complex cancer or complex drug resistance progression; provides guidance for further adjustment of drug use; and establishes a multidisciplinary cooperative team, improves the quality of clinical diagnosis and treatment, and optimizes the process of medical services.